Analisis Legal Tender Uang Digital Bank Sentral Indonesia - Baharudin Vanani, Alvin; Suselo, Dedi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to analyze Indonesia’s Central Bank Digital money as a legitimate digital currency. This study uses descriptive qualitative research methods that describe objects in the form of journals, books, news, and articles published on the internet in order to obtain the necessary data. Based on the result of the study, it was found that the issuance of gigital money did not only consider the rapid growth of cryptocurrencies, but also on the declining use of cash, limited banking services and the diversity of payment types. Because digital money is one of the currencies issued by the central bank, its legality has been regulated and guaranteed by the central bank. It has a value and underlying that is equivalent to cash so that digital money can be used as a solution for all forms of innovation an transaction demands in the era of technological and cryptocurrency advancements.